Training time scheduler for Zimasco Shurugwi and south Dyke division - Mudenge, Tinashe (Midlands State University, 2018)
The basis of this project was to develop a Training time Scheduler for Zimasco Shurugwi and South dyke division (Training department). The main focus of the system is to try to curb problems that are associated with scheduling of courses, facilitators and venues throughout the whole year. Every year end the department gathers necessary training information from the training needs and begin the scheduling process. This is done on a spreadsheet on rows and columns. To derive an annual training plan it demands a dedicated three weeks (working hour basis) at most. With this at hand it has created an opportunity for me to have an in-depth research on how to computerize and ease the burden that the training department is experiencing. There were various fact gathering methodologies that were carried out to come up with a comprehensive detail of how the manual system works, the challenges that they face and also their hopes of computerization. The results of the fact gathering clearly highlighted that surely there is a need for developing a computerized training time scheduler that meets the current problems. The system development process came just on time, when Zimasco was upgrading to Microsoft Office 2010. The upgrade managed to integrate the Microsoft Outlook with the training time scheduler allowing the system to auto-generate notifications that will be send to users once scheduled for an event. The training department adopted the final application and have implemented it on a parallel run to evaluate its benefit. Time and resources were a major drawback to many modifications and enhancements to the system hence I recommend that more time and resources must be given to work on additional modules such as incorporating an sms gateway that automatically notifies specific users over mobile networks. After the system has been fully appreciated it then calls for the department to implement it in other divisions.